HLA allele and haplotype frequencies of eight Indian populations based on 130,518 registered stem cell donors - Solloch, Ute V.; Kaniyath Madhusoodhanan, Chinma; Lange, Vinzenz; Sauter, Jürgen; Jagannathan, Latha; Paul, Patrick; Fernández-Viña, Marcelo A.; Schmidt, Alexander H. (Frontiers in Immunology, 2025)
IntroductionIn hematopoietic stem cell transplantation, optimal results are achieved when donors and patients are matched regarding their human leukocyte antigen (HLA) genes. Population-specific HLA allele and haplotype frequency distributions determine the probabilities to find matched donors in a stem cell donor registry of given size and ethnic composition.MethodsTo evaluate the needs of Indian patients with regard to future donor recruitment, we analyzed a large data set of n=130,518 potential stem cell donors registered with DKMS-BMST, a Bangalore-based donor registry with nationwide donor recruitment activities. We defined 8 subpopulations by native language and state of origin of both parents. The subpopulations comprised four samples belonging to the Dravidian language family (native language: Kannada/state of origin: Karnataka, Tamil/Tamil Nadu, Telugu/Andhra Pradesh and Malayalam/Kerala), and four samples belonging to the Indo-Aryan language group (Bengali/West Bengal, Gujarati/Gujarat, Hindi/Uttar Pradesh, Marathi/Maharashtra). The precise definition of subpopulations and large sample sizes between n=5,808 (Telugu/Andhra Pradesh) and n=14,866 (Malayalam/Kerala) are strengths of our study. Our results regarding HLA allele and haplotype frequencies refine published data.Results and DiscussionIn terms of genetic relatedness, we observed a division of the subpopulations into a Southern and a Northwestern Indian cluster and the Bengali/West Bengal sample which differed significantly from the seven other subpopulations. Patients from Southern Indian populations are the main beneficiaries from the DKMS-BMST registry in the current ethnic composition. A more even nationwide coverage will be achieved in the future with the opening of local recruitment offices in different parts of India.